Characterization of two novel HIV-1 second-generation recombinants (CRF01_AE/CRF07_BC) identified in Hebei Province, China - Yang, Xuegang; Zhao, Na; Su, Miaomiao; Meng, Juan; Du, Jian; An, Weina; Shi, Haoxi; Fan, Weiguang (Frontiers in Microbiology, 2023)
Unlike the circulating recombinant forms (CRFs), the unique re-combinant forms (URFs) of HIV-1 consist of a mixture of subtypes, and each URF has a unique breakpoint. In this study, we identified the near full-length genome (NFLG) sequences of two novel HIV-1 URFs (Sample ID: BDD034A and BDL060) isolated during HIV-1 molecular surveillance in 2022 in Baoding city, Hebei Province, China. To analyze the genetic recombination patterns and breakpoints of these two NFLG sequences, phylogenetic trees were constructed and their subregions were analyzed. Phylogenetic analysis indicated that these two NFLG sequences formed unique monophyletic branches that did not cluster with other HIV-1 subtypes. Recombinant breakpoint analysis revealed that the NFLGs of BDD034A and BDL060 were composed of CRF01_AE and CRF07_BC, containing seven segments, respectively. For BDD034A, three CRF01_AE fragments were inserted into the CRF07_BC main framework, whereas for BDL060, three CRF07_BC fragments were inserted into the CRF01_AE main framework. The emergence of the CRF01_AE/CRF07_BC recombinant strains indi-cates that HIV-1 co-infection is common. The increasing genetic com-plexity of the HIV-1 epidemic in China warrants continued investiga-tion.